Intraperitoneal Gemcitabine Chemotherapy Treatment for Patients with Resected Pancreatic Cancer: Rationale and Report of Early Data. (12th December 2011) - Sugarbaker, Paul H.; Stuart, O. Anthony; Bijelic, Lana
Abstract : Currently, the surgical management of pancreas cancer is recognized around the world as inadequate. Despite a potentially curative R0 resection, long-term survival is rare. There is a strong rationale for the use of chemotherapy in the operating room to reduce local-regional of recurrent/progressive disease. Gemcitabine monotherapy administered by an intraperitoneal route in the operating room with hyperthermia and then for long-term treatment postoperatively has a pharmacologic basis in that the exposure of peritoneal surfaces to intraperitoneal gemcitabine is approximately 200–500 times the exposure that occurs within the plasma. A standardized treatment with intraoperative and long-term chemotherapy that is well tolerated would greatly facilitate further improvements in pancreas cancer treatment and may lead the way to an evolution of more successful treatment strategies of this dread disease. The aim of this paper is to present the early data on a protocol in progress in patients with resected pancreatic cancer.